2017
DOI: 10.1016/j.brainresbull.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A novel pleiotropic effect of aspirin: Beneficial regulation of pro- and anti-inflammatory mechanisms in microglial cells

Abstract: Aspirin, one of the most widely used non-steroidal anti-inflammatory drugs, has extensively studied effects on the cardiovascular system. To reveal further pleiotropic, beneficial effects of aspirin on a number of pro- and anti-inflammatory microglial mechanisms, we performed morphometric and functional studies relating to phagocytosis, pro- and anti-inflammatory cytokine production (IL-1β, tumor necrosis factor-α (TNF-α) and IL-10, respectively) and analyzed the expression of a number of inflammation-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…The expression levels were shown in Additional file 11 : Figure S5. The results indicated that some of the potentially targeted genes, like C4BPA [ 35 ], MASP1 [ 36 ], MBL2 [ 37 ], ORM1 [ 38 ], APOA2 [ 39 ], KNG1 [ 40 ], are significantly downregulated upon knocking down the lncRNAs (Fig. 5a and Additional file 12 : Figure S6a),.On the contrary, the expression of these genes except for ORM1 appeared significantly increased when we overexpressed APOC1P1 in CCA cell line (Additional file 12 : Figure S6b and c), suggesting that the inflammatory genes could be regulated by the selected lncRNAs in CCA cells.…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels were shown in Additional file 11 : Figure S5. The results indicated that some of the potentially targeted genes, like C4BPA [ 35 ], MASP1 [ 36 ], MBL2 [ 37 ], ORM1 [ 38 ], APOA2 [ 39 ], KNG1 [ 40 ], are significantly downregulated upon knocking down the lncRNAs (Fig. 5a and Additional file 12 : Figure S6a),.On the contrary, the expression of these genes except for ORM1 appeared significantly increased when we overexpressed APOC1P1 in CCA cell line (Additional file 12 : Figure S6b and c), suggesting that the inflammatory genes could be regulated by the selected lncRNAs in CCA cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that deletion of Kng1 protein in ischemic mice reduced thrombosis and inflammation (Langhauser et al, 2012 ). Also Kng1 as a pro-inflammatory cytokine, Which promotes the development of cellular inflammation (Langhauser et al, 2012 ; Kata et al, 2017 ). In this study, STRING database revealed that Kng1 is a downstream target gene of Ednrb.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were allowed to adapt to the environment for one week before the experiments. Animal experimental procedures were performed according to the Guide for Care and Use of Laboratory Animals ( 15 , 16 ) and protocols were approved by the Animal Experiment Ethics Committee of The First People's Hospital (Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%